Transplante singênico e xenogênico de espermatogônias-tronco em tilápias-nilóticas (Oreochromis niloticus) adultas - Samyra Maria dos Santos Nassif Lacerda (2010)
Germ cell transplantation consists in the removal of spermatogonial stem cells from the testis of a donor animal and the transferring of them into the testis of a recipient animal, where these cells will develop to form mature spermatozoa presenting donor genetic characteristics. This technique is the only available approach to functionally investigate the spermatogonial stem cell biology in mammals and even in other vertebrates. Although is well characterized in mammals, this is the first successful report of a non-surgical methodology for spermatogonial transplantation directly into the testes of adult fish. Using the Nile tilapia (Oreochromis niloticus) as model, nine weeks after transplantation we demonstrated the production of donor spermatozoa in the recipient testis, in which endogenous spermatogenesis had been depleted with the cytostatic drug busulfan. In addition, through microsatellite DNA analysis, we verify the generation of progeny with individuals presenting the genotype of donor animals, which belonged to a different strain of Nile tilapia (Red tilapia). Similarly, after transplantation, cryopreserved tilapia spermatogonia were able to proliferate and differentiate into spermatozoa in the embryos and larvae, these results indicate that spermatogonial transplantation in sexually mature fish may facilitate and reduce considerably the time needed to obtain viable gametes and offspring with donor genotype. The suitability of adult males of tilapia as a recipient model for xenogenic transplantation was also demonstrated using spermatogonial stem cell derived from other teleost species (tucunaré, Cichla monoculus) and vertebrate species belonging to different classes (bullfrog, Lithobates catesbeianus; rat, Rattus norvegicus). In this type of transplantation, the exogen spermatogonia were able to colonize and proliferate in the testes of tilapia, thus demonstrating the plasticity of the seminiferous tubules environment in this species of teleost. Therefore, a new and viable methodology of spermatogonial transplantation was established, providing a totally new and quite promising scenario for investigation of the spermatogonial stem cell biology and testicular function in teleosts and other vertebrates, also presenting potential applications in biotechnology, conservation and production in aquaculture.